Geomorphic Evidence of Postglacial Terrestrial Environments on Atlantic Canadian Continental Shelves - Shaw, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractChanges in the geography of Atlantic Canada since the last glacial maximum (LGM) are grouped into three phases. The first phase (LGM – ca. 13 ka BP) commences with glaciers at the edge of the continental shelves, and ends with the glaciers having retreated to near modern coasts. In the second phase (ca. 13 ka BP‑10 ka BP), glaciers were mainly on land; on the continental shelves there were scattered small ice caps and an outer-shelf archipelago. Early in phase three, beginning ca. 10 ka BP, glaciers were largely absent, and the archipelago was gradually submerging; elsewhere, falling relative sea levels caused emergence. Multibeam sonar mapping has revealed the geomorphic evidence of submerged terrestrial environments of phases II and III, including fluvial, deltaic, and coastal systems. The best-preserved fluvial systems are in Northumberland Strait and the Bras d’Or Lakes. Elsewhere, multibeam bathymetric data allow discrimination between fluvial and non-fluvial channels. Deltas were mainly preserved in the special circumstances of Newfoundland fjords. Submerged coastal systems are common in the Bras d’Or Lakes, but rare elsewhere. Landscape preservation is ascribed to special circumstances. Paleogeographic reconstructions have applications in the field of evolutionary biology and archaeology.